ADAM10 overexpression shifts lympho- and myelopoiesis by dysregulating S2/S3 cleavage products of Notch - Gibb, David R. (J Immunol, 2011)
Although the physiological consequences of Notch signaling in hematopoiesis have been extensively studied, the differential effects of individual notch cleavage products remain to be elucidated. Given that ADAM10 is a critical regulator of Notch and that its deletion is embryonically lethal, we generated mice that overexpress ADAM10 (A10Tg) at early stages of lympho- and myeloid development. Transgene expression resulted in abrogated B cell development, delayed T cell development in the thymus and unexpected systemic expansion of CD11b(+)Gr-1(+) cells, also known as myeloid-derived suppressor cells (MDSCs). Mixed bone marrow reconstitution assays demonstrated that transgene expression altered hematopoiesis via a cell intrinsic mechanism. Consistent with previously reported observations, we hypothesized that ADAM10 overexpression dysregulated Notch by uncoupling the highly regulated proteolysis of Notch receptors. This was confirmed using an in vitro model of hematopoiesis via culturing A10Tg hematopoietic Lineage(−)Sca-1(+)c-Kit(+) cells (LSKs) with OP-9 stromal cells in the presence or absence of Delta-1 (OP9-DL1), a primary ligand for Notch. Blockade of the S2 and S3 cleavage of the Notch receptor demonstrated differential effects on hematopoesis. OP9-DL1 cultures containing the ADAM10 inhibitor (S2 cleavage site) enhanced and rescued B cell development from wild type and A10Tg LSKs, respectively. In contrast, blockade of γ-secretase at the S3 cleavage site induced accumulation of the S2 product and consequently prevented B cell development and resulted in myeloid cell accumulation. Collectively, these findings indicate that the differential cleavage of Notch into S2 and S3 products regulated by ADAM10 is critical to hematopoietic cell-fate determination.